Children's Drawing of Plant Life in the Time of COVID-19: An Analysis of the Changes Related to Content and Colour over a Two-Year Period - Ilargi Zaballa; Maria Merino; José Domingo Villarroel (MDPI AG, 2022)
This study analyses the depictions that a sample of young children completed to express their knowledge of plant life at two different times, two years apart. The pictorial content is examined by the complexity of the depictions of flora as well as the range of colour that the children in the sample chose. The study presents the changes that occurred in the children's illustrations of plants after 24 months. The conclusions are discussed in view of the data that preceding studies provide on the subject of botanical literacy in childhood, and raise the hypothesis that the unexpected results obtained in the study might reflect a learning loss in the understanding of the plant world as a consequence of the school closures that followed the outbreak of the COVID-19 pandemic.